Study on Band Gaps of the Photonic Crystal in THz Frequency Range Based on the Periodic WCS-PSTD Method - Chen, Juan; Zhang, Anxue; Li, Jianjun (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a periodic weakly conditionally stable -pseudospectral time domain (WCS-PSTD) method is presented to simulate photonic crystal in Terahertz frequency range. The time step size in this method is only determined by the mesh length -z and the spatial discretization along the z direction only needs two cells per minimum wavelength. The 3D formulas of the method are presented and the time stability condition of the method is demonstrated. Numerical results show that this method is more efficient than the periodic finite difference time domain (FDTD? method in terms of computer memory and computation time.